تحليل أسباب الازدحام المروري في مدينة الزاوية: دراسة حالة خلال ساعات الذروة (Comprehensive Journal of Science, 2025)
This study aims to analyze the causes of traffic congestion in the city of Al-Zawiya during peak hours through a descriptive and analytical approach based on field observation and analysis of influencing factors.Main routes such as the  Coastal Road ,Jamal Abdel Nasser Street, and the  University Intersection  were selected as case areas.Results indicate that the increase in private vehicles, weak public transport, lack of parking spaces, and inefficient signal management are the main contributors to congestion.The study recommends developing an efficient public transport system and applying intelligent traffic management solutions to improve mobility and sustainability.